Universal Typeface. Innovation without Style - Dario Russo (Agathón)
The Bauhaus (1919-1933) has marked history. This school was animated by some of the most significant Twentieth-century artist-designers, from Gropius to Kandinskij, from Itten to Moholy-Nagy, not related to an unambiguous approach. However, the idea of the Bauhaus, which innervated the debate and the practice of the project in Europe and in the USA (and beyond) for decades, has resulted into some kind of International Style which, in typography, corresponds to the Universal typeface of Herbert Bayer (1925). This article aims to highlight how the universal typeface, that today represents the ‘style’ of Modernity, was in the beginning innovation in its purest: a configuration aimed at effect, to achieve maximum result with minimum effort, both from an economic and technical-productive, and from a functional point of view, readability and visual perception; and how the most interesting aspect is not the form itself – re-proposed, equal to itself, for almost a century – but its underlying design principle.